PENGARUH STRATEGI PEMASARAN KREDIT, PROSEDUR PEMBERIAN KREDIT, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH - Firmansyah, Dicky Wahyu; Bhirawa, Sigit Wisnu Setya; Damayanti, Susi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2025)
The purpose of this study was to determine the effect of credit marketing strategies, credit granting procedures and service quality on customer satisfaction. This study used an associative quantitative technique. The sampling technique used was purposive sampling with 79 customers. The analytical tool used was SPSS for Windows version 25. The test techniques used were validity tests, reliability tests, classical assumptions, multiple linear regression analysis, t-tests, F-tests and coefficients of determination. The results showed that the variables of credit marketing strategies, credit granting procedures and service quality had a significant effect, both partially and simultaneously, on customer satisfaction at BPR Nusumma Kediri.